Phylogenetic Study of Zebrafish (Amatitlania nigrofasciata) as an Introduction Spesies in Buyan Lake - Pratama, Bachori Dhian; Julyantoro, Pande Gde Sasmita; Pratiwi, Made Ayu (Journal of Marine and Aquatic Sciences; Vol 5 No 1 (2019)DO - 10.24843/jmas.2019.v05.i01.p17, 2018)
Buyan Lake has some fishery commodities which were often encountered include the Zebrafish ( Amatitlania nigrofasciata ). The origin existence of Zebrafish in Buyan Lake is not yet known then it needs study in order to know the certainty of species, phylogenetic, haplotype diversity, and phenotype characteristic. The study was conducted from January to February 2018. Molecular identification was done at Laboratory of Biodiversity Indonesia Bali. This research used quantitative and qualitative descriptive methods. Sampling was done by simple random sampling from fisherman catches. Zebrafish’s fin samples were used for molecular identification and Zebrafish’s morphological for morphological identification. The results showed that the entire sequence samples were successfully amplified with the Cytochrome Oxidase subunit I (COI) gene of 620 bp. The genetic distance in the entire Zebrafish sequences in Buyan Lake of 0 which means that the sequence of all samples are exactly similiar as species of Amatitlania nigrofasciata with the genetic distance calculation of 0. Sequence of Zebrafish in Buyan Lake is closely related to Amatitlania nigrofasciata KU568740, Amatitlania nigrofasciata KU568739, Amatitlania nigrofasciata KU568737, Amatitlania nigrofasciata KJ552531, and Amatitlania nigrofasciata KU568738 with genetic distance of 0 and has a distant relation with Rocio ostofasciata EU751752 with genetic distance of 0.113. The haplotype diversity of Zebrafish sequences in Buyan Lake showed the value of 0 which belongs to a low haplotype diversity. Black and Black Zebrafish with Red Spotted are in a different clade with Albino and Albino Zebrafish with Red Spotted with bootstrap value of 100, means they have phenotypically differences.